Association of Life's Essential 8 with osteoarthritis in United States adults: mediating effects of dietary intake of live microbes - Gou, Ruoyu; Chang, Xiaoyu; Li, Zeyuan; Pan, Ying; Li, Guanghua (Frontiers in Medicine, 2023)
Objective Osteoarthritis (OA) is associated with cardiovascular disease, and represents a persistent economic and physical burden on patients in the United States. This study evaluated the mediating effect of dietary live microbe intake on the association between cardiovascular health (based on Life’s Essential 8 [LE8] scores) and osteoarthritis (OA) in adults. Methods This cross-sectional study included data from the National Health and Nutrition Examination Survey, 1999-2019 (from patients aged ≥ 20 years). LE8 scores (0-100) were measured according to the American Heart Association definition and categorized as low (0-49), moderate (50-79), or high (80-100). OA disease status was assessed using self-reported data from patients. The relationships were evaluated using multivariate logistic and restricted cubic spline models. Mediation analysis was used to evaluate the mediating effect of dietary live microbe intake on the association between LE8 and OA risk. Results The study included 23,213 participants aged ≥ 20 years. After adjusting for latent confounders, higher LE8 scores were found to be associated with a lower incidence of OA. The odds ratios (with 95% confidence intervals) for low, moderate, and high OA risk were: 0.81 (0.69, 0.96), and 0.55 (0.44, 0.69), respectively; a nonlinear dose-response relationship was observed (P-nonlinear = 0.012). Health behavior and factor scores showed a similar pattern of correlation with OA risk. Low live microbe intake mediated the association between LE8, health behavior, and health factor scores with OA risk, and did not appear to reduce OA risk. Conclusions Our findings suggest that although higher LE8 scores reduce the risk of developing OA, low live microbe intake may reduce the protective effect of higher scores. It is therefore essential to emphasize adherence to a lifestyle that confers high LE8 scores. Individuals should also be advised to reduce the intake of foods with low live microbe content.